Sufisme dan Kemiskinan Kultural pada Komunitas Nelayan di Pesisir Teluk Bone Kecamatan Sibulue - Andi Agustang (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2010)
This article deals with the relationship between ascetism as practiced by the followers of Tarekat Khalawatiyah Yusuf in Bone, one of major Sufi orders (tariqah) in South Sulawesi and their fatalistic and pessimistic attitude towards worldly works and achievements which, in turn, brings them to a situation which is classified in Sociology as “cultural poverty.” From the field research conducted by the author in Kecamatan SibuluE where the doctrines and practices of the Khalawatiyah Yusuf Sufi order are practiced firmly by its followers among fishermen in the area, it is found that a spiritual quest and even spiritual greed leading to various mystical experience has led the fishermen to abandon the importance of hard work and realistic optimism for material gain and possession. This happans because they tend to put themselves into an absolute dependence on the will of God forth eir destiny and subordination of reason and human own action in managing their worldly life. In other words, the followers of the tariqah among the fishermen of SibuluE put themselves into a fatalistic way of life, submissive to predetermined fate, and to denounce a worldly life, an attitude that has in fact led them to a sort of cultural and economic poverty.